Zadanie 1. Opuść nawiasy, a następnie zredukuj wyrazy podobne.
a) 7 + (5x + 4)
b) 3x + (y – 2x)
c) (4 – 2x) + (7x – 2)
d) (4a – 7b) + (2a + 3b)



Zadanie 2. Opuść nawiasy, a następnie zredukuj wyrazy podobne.
a) 2a – (3a – 7)
b) – (2x – 3 ) – x
c) (2p – 1) – ( 3 + 5p)
d) – (2x – 1) – (3x + 1)
e) (2m + 4n) – (m – 0,5n)


Odpowiedź :

Hej!

Zadanie 1 :

7 + (5x + 4) = 7 + 5x + 4 = 5x + 11

3x + (y - 2x) = 3x + y - 2x = x + y

(4 - 2x) + (7x - 2) = 4 - 2x + 7x - 2 = 5x - 2

(4a - 7b) + (2a + 3b) = 4a - 7b + 2a + 3b =

= 6a - 4b

Zadanie 2 :

2a - (3a - 7) = 2a - 3a + 7 = -a + 7

-(2x - 3) - x = -2x + 3 - x = -3x + 3

(2p - 1) - (3 + 5p) = 2p - 1 - 3 - 5p = -3p - 4

-(2x - 1) - (3x + 1) = -2x + 1 - 3x - 1 = -5x

(2m + 4n) - (m - 0,5n) = 2m + 4n - m + 0,5n =

= m + 4,5n

Pozdrawiam! - Julka